A Comparative Study of Chinese and Myanmar Honorific Titles - Swe, Han Nwe (Technium Social Sciences Journal, 2021)
Honorific titles, as an essential part of speech communication, occur in all languages. But due to the cultural diversity, there are many different laws and regularities in the choice of them. This paper is the comparative study of the characteristics of Chinese and Myanmar honorific titles and their pragmatic rules to reduce the barriers in language communication.